2013
DOI: 10.1088/0960-1317/23/3/035009
|View full text |Cite
|
Sign up to set email alerts
|

Seamless integration of CMOS and microfluidics using flip chip bonding

Abstract: We demonstrate the microassembly of PDMS (polydimethylsiloxane) microfluidics with integrated circuits made in complementary metal-oxide-semiconductor (CMOS) processes. CMOS-sized chips are flip chip bonded to a flexible polyimide printed circuit board (PCB) with commercially available solder paste patterned using a SU-8 epoxy. The average resistance of each flip chip bond is negligible and all connections are electrically isolated. PDMS is attached to the flexible polyimide PCB using a combination of oxygen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 17 publications
0
41
0
Order By: Relevance
“…The use of soft lithography enabled micrometer-scale fluid channels to be incorporated onto the IC’s surface, as opposed to a millimeter-scale “bath-tub” channels used in previous studies. 4,21 These lithographically defined channels allow the position of cells to be controlled with high accuracy and for them to be brought into close proximity to sensors for highly sensitive measurement. The combination of soft lithography with laser micromachining, allowed these millimeter-sized PDMS pieces to be connected to one another with fluid channels and to be supplied with fluid connections to the outside world.…”
Section: Discussionmentioning
confidence: 99%
“…The use of soft lithography enabled micrometer-scale fluid channels to be incorporated onto the IC’s surface, as opposed to a millimeter-scale “bath-tub” channels used in previous studies. 4,21 These lithographically defined channels allow the position of cells to be controlled with high accuracy and for them to be brought into close proximity to sensors for highly sensitive measurement. The combination of soft lithography with laser micromachining, allowed these millimeter-sized PDMS pieces to be connected to one another with fluid channels and to be supplied with fluid connections to the outside world.…”
Section: Discussionmentioning
confidence: 99%
“…The ISFET used for measuring the cell culture demonstrates a drift which is shown in the figure 1c. Cell growth requires precise control over the pH [6], and threshold voltage shifts might cause errors in the measurements. To mitigate this drift, it was shown that cycling the vertical electric field resets the threshold voltage drift [11].…”
Section: Drift and Pulse Width Modulation Circuitmentioning
confidence: 99%
“…Their commercial use has been limited due to the fact that they have an intrinsic threshold voltage drift [5] and challenges in packaging [6]. There has been substantial research to investigate the cause of the drift [7] [8] [9], but some of the factors causing the drift have not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Also, CMOS technology leads to a totally electronic integrated lab-on-a-chip utilizing a homogenous technology [8,9]. CMOS is an innovation used in building integrated circuits.…”
Section: Introductionmentioning
confidence: 99%